2022
DOI: 10.1021/jacs.2c02596
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizer Encryption with Aggregation Enhanced Singlet Oxygen Production

Abstract: Chromophores that generate singlet oxygen ( 1 O 2 ) in water are essential to developing noninvasive disease treatments using photodynamic therapy (PDT). A facile approach for formation of stable colloidal nanoparticles of 1 O 2 photosensitizers, which exhibit aggregation enhanced 1 O 2 generation in water toward applications as PDT agents, is reported. Chromophore encryption within a fuchsonarene macrocyclic scaffold insulates the photosensitizer from aggregation induced deactivation pathways, enabling a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 111 publications
0
19
0
Order By: Relevance
“…As shown in Figure S23, for Fe 1 /ND SAC, after adding 1 O 2 quencher, 2,2,6,6-tetramethyl-4-piperidinyloxyl (TEMP), into reaction system, no degradation activity of TC was observed. Meanwhile, in the corresponding EPR results (Figure d and Figure S24), three obvious peaks ascribed to TEMP- 1 O 2 species were identified. Nevertheless, after introducing 5,5-dimethyl-1-pyrroline N -oxide (DMPO) to capture • OH, • SO 4 – and • O 2 – , only a weak DMPO- • OH signal emerged and there was scarcely any characteristic peak for • SO 4 – or • O 2 – . These results suggested that the 1 O 2 active species was solely generated in Fe 1 /ND-PMS system.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S23, for Fe 1 /ND SAC, after adding 1 O 2 quencher, 2,2,6,6-tetramethyl-4-piperidinyloxyl (TEMP), into reaction system, no degradation activity of TC was observed. Meanwhile, in the corresponding EPR results (Figure d and Figure S24), three obvious peaks ascribed to TEMP- 1 O 2 species were identified. Nevertheless, after introducing 5,5-dimethyl-1-pyrroline N -oxide (DMPO) to capture • OH, • SO 4 – and • O 2 – , only a weak DMPO- • OH signal emerged and there was scarcely any characteristic peak for • SO 4 – or • O 2 – . These results suggested that the 1 O 2 active species was solely generated in Fe 1 /ND-PMS system.…”
Section: Resultsmentioning
confidence: 99%
“…A photosensitizer (PS) is needed for PDT. Under the excitation of a laser, the PS converts the oxygen into reactive oxygen species (ROS), many of which are singlet oxygen ( 1 O 2 ) species. Porphyrin-based PSs account for a large proportion of PSs. They are mainly divided into hematoporphyrins, metalloporphyrins, , porphycenes, , pheophorbides, , purpurins, chlorins, , protoporphyrin, , and phthalocyanines. , These porphyrin PSs have shown prodigious potentials in PDT, and some of the porphyrin derivatives (e.g., Photofrin, Visudyne, and Foscan) have been approved by the Food and Drug Administration (FDA) and applied in the clinic. Although porphyrin PSs possess good biosafety and a suitable biological wavelength window (650–900 nm) for deep tissue penetration, their poor water solubility significantly lowers 1 O 2 generation in physiological solution and thereby limits their biomedical applications. , Hence, various strategies were proposed to enhance the water solubility of the porphyrin PSs.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, an ideal PS is expected to possess the necessary virtues, including a straightforward synthetic approach, high chemical purity, excellent biocompatibility and water solubility [ 13 ]. In recent years, a series of PSs have been fabricated, greatly facilitating the development of PDT techniques [ 14 , 15 , 16 , 17 , 18 ]. Moreover, dual or multi-modal treatment strategies with stimuli-responsive drug delivery have demonstrated satisfactory anticancer performance, such as PDT combined with chemotherapy [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%